The translation of idioms in George Orwell's “Animal Farm” into Arabic / Kareema Abdulnabi Lafta - Lafta, Kareema Abdulnabi (2015)
This study aims to investigate the phenomenon of idioms, their types, the strategies applied in translating them and how effectively they are rendered in the English novel “Animal Farm” and its Arabic version “يضسػح انؽٛ إٌ ” Mazraat (Farm) Al-haywan (Animal). The objectives of this study are: (i) to investigate the strategies used in translating the idioms in Orwell‟s “Animal Farm” into Arabic, (ii) to find out if the idioms in the English source text are effectively translated into Arabic, and (iii) to find the most suitable strategies for conveying the idioms that have been translated inappropriately from English into Arabic. The study employs Fernando‟s (1996) classification of idioms and Baker‟s (2011) proposed strategies for translating idioms. In addition, Nida‟s (1964) notion of equivalence in translation has been applied to determine how the idioms are effectively translated into the equivalent Arabic idioms and expressions. Forty idioms from the English novel and their translation in the book‟s Arabic version were extracted. Discussions on the findings include the excerpts of both novels which are analyzed thoroughly. The findings have revealed that 40% of the extracted idioms are translated using the paraphrase strategy; while 25% are translated by corresponding TT idiomatic expressions; 10% are translated by idiom of similar meaning but dissimilar form; and 5% by omission of the entire idiom. The findings have also shown that the message was considered effectively conveyed in 87.5% of the analyzed data; and less effectively conveyed in 10%; while the translated message was found to be distorted in only 2.5%. Moreover, the study has demonstrated that the most suitable strategy for conveying an inappropriately translated idiom is to use Baker‟s (2011) strategy of translating an idiom with an idiom of similar meaning but dissimilar form.